2012
DOI: 10.1029/2012gl052249
|View full text |Cite
|
Sign up to set email alerts
|

First measurements of radar coherent scatter by the Radio Aurora Explorer CubeSat

Abstract: [1] The Radio Aurora Explorer CubeSat detected the first radar echoes during the solar storm of March 8, 2012. The 300 s ground-to-space bi-static radar experiment was conducted in conjunction with the Poker Flat Incoherent Scatter Radar in the local morning ($8 am) over Poker Flat, Alaska. The geomagnetic conditions for the E region field-aligned irregularity generation were optimal due to strong (about 1500 m/s) F region ion drifts and sufficient E region ionization (electron densities were $2 Â 10 11 m À3 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…These threshold observations parallel those made in the comparisons of in situ sounding rocket electric field and ground‐based imaging radar data during the two Joule campaigns in Alaska [ Bahcivan et al , ; Hysell et al , ]. Although not discussed here, in a previous paper [ Bahcivan et al , ], we reported that the phase velocity obeys the empirical formula C s cos θ . To our knowledge, the profiles shown in Figure provide the first altitudinally resolved estimates of magnetic aspect sensitivity of submeter‐scale auroral irregularities. The backscatter is confined to the altitude range of 106–112 km (3 dB points), as seen on Figure (left).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These threshold observations parallel those made in the comparisons of in situ sounding rocket electric field and ground‐based imaging radar data during the two Joule campaigns in Alaska [ Bahcivan et al , ; Hysell et al , ]. Although not discussed here, in a previous paper [ Bahcivan et al , ], we reported that the phase velocity obeys the empirical formula C s cos θ . To our knowledge, the profiles shown in Figure provide the first altitudinally resolved estimates of magnetic aspect sensitivity of submeter‐scale auroral irregularities. The backscatter is confined to the altitude range of 106–112 km (3 dB points), as seen on Figure (left).…”
Section: Discussionsupporting
confidence: 87%
“…These threshold observations parallel those made in the comparisons of in situ sounding rocket electric field and ground‐based imaging radar data during the two Joule campaigns in Alaska [ Bahcivan et al , ; Hysell et al , ]. Although not discussed here, in a previous paper [ Bahcivan et al , ], we reported that the phase velocity obeys the empirical formula C s cos θ .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On 8 March 2012, RAX-2 recorded the first FAI-related echo [33]. The experiment was conducted with PFISR, and the resulting rangetime-intensity plot is shown in Fig.…”
Section: Rax-2 Was Launched On 28mentioning
confidence: 99%